Pursuit of the New: Louise Hanson-Dyer, Publisher and Collector. - Rodmell, Paul (Music & Letters, 2025)
This collection of twelve essays focuses on Louise Hanson-Dyer, an influential Australian music publisher who founded Editions de l'Oiseau-Lyre in 1932, notable for producing France’s first LPs and publishing definitive editions of composers such as François Couperin. Hanson-Dyer, a prominent social figure with extensive international connections, operated in the male-dominated fields of music publishing and recording, supporting a wide range of musical and artistic activities primarily in France and Australia. The volume explores her multifaceted career, including her involvement in concert organizations, art collecting, and her distinctive approach to music publication design. While the essays highlight her significant impact on musicology and cultural exchange, they also address her complex personality and the challenges she faced as a woman asserting authority in her field. Overall, the work underscores Hanson-Dyer’s lasting influence on music publishing and her role in shaping transnational cultural networks in the early to mid-20th century.